2019
DOI: 10.1093/neuonc/noz011
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor DNA methylation heterogeneity in glioblastoma: implications for DNA methylation-based classification

Abstract: Background A feature of glioblastoma (GBM) is cellular and molecular heterogeneity, both within and between tumors. This variability causes a risk for sampling bias and potential tumor escape from future targeted therapy. Heterogeneous intratumor gene expression in GBM is well documented, but little is known regarding the epigenetic heterogeneity. Variability in DNA methylation within tumors would have implications for diagnostics, as methylation can be used for tumor classification, subtyping, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 44 publications
3
89
0
1
Order By: Relevance
“…Methylation analysis and normalization was performed as previously described [21]. Briefly, methylation data were processed with the statistical software R (version 3.6.1) using the Minfi [22] and ChAMP [22][23][24] packages.…”
Section: Dna Methylation Arraymentioning
confidence: 99%
“…Methylation analysis and normalization was performed as previously described [21]. Briefly, methylation data were processed with the statistical software R (version 3.6.1) using the Minfi [22] and ChAMP [22][23][24] packages.…”
Section: Dna Methylation Arraymentioning
confidence: 99%
“…By self-renewal of stem cell like neoplastic cells, genetically and phenotypically diverse daughter cells develop, from which different intratumoral subtypes arise [ 9 , 10 ]. Besides these two main hypotheses, it is assumed that tumor heterogeneity is a consequence of a multifactorial process, including epigenetic alterations [ 11 ], intercellular communication, and interaction with the surrounding microenvironment [ 10 , 12 ]. In addition to regional heterogeneity, a chronological heterogeneity can also be observed when comparing pairs of primary and recurrent GBM.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported intratumor DNA methylation-based subtype heterogeneity in five of twelve glioblastomas in their cohort 24 . We were unable to confirm this extent of heterogeneity in our study.…”
Section: Discussionmentioning
confidence: 99%